'Smoking' mephedrone: The identification of the pyrolysis products of 4‐methylmethcathinone hydrochloride. Issue 5 (28th May 2012) - Kavanagh, Pierce; O'Brien, John; Power, John D; Talbot, Brian; McDermott, Seán D
Abstract : The ring‐substituted cathinone – mephedrone – has gained popularity among recreational drug users over the past several years. It is generally consumed orally or by snorting but reports indicate that it is also ingested by vaporization/inhalation. This study examines the pyrolysis products produced by heating mephedrone under using simulated 'meth pipe' conditions. Thirteen pyrolysis products were identified, the major ones being iso ‐mephedrone, 4‐methylpropiophenone, 4‐methylphenylacetone, two pyrazine derivatives formed by dimerization of mephedrone, N ‐methylated mephedrone ( N, N, 4‐trimethylcatinone), two hydroxylated oxidation products and a diketone. Other minor products formed were identified as 4‐methylacetophenone, two α‐chloro ketones and N ‐methylated iso ‐mephedrone. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The substituted cathinone, mephedrone, is generally consumed orally or by snorting but reports indicate that it is also ingested by vaporization/inhalation ('smoking'). This study examines the pyrolysis products produced by heating mephedrone under using simulated 'meth pipe' conditions. A variety of compounds are produced and there is evidence of thermal rearrangement, methylation, condensation/dimerization, halogenation and oxidative degradation.